2016
DOI: 10.1074/jbc.m116.729343
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Mutations in the Valosin-containing Protein/p97(VCP) N-domain Inhibit the SUMOylation of VCP and Lead to Impaired Stress Response

Abstract: Valosin-containing protein/p97(VCP) is a hexameric ATPase vital to protein degradation during endoplasmic reticulum stress. It regulates diverse cellular functions including autophagy, chromatin remodeling, and DNA repair. In addition, mutations in VCP cause inclusion body myopathy, Paget disease of the bone, and frontotemporal dementia (IBMPFD), as well as amyotrophic lateral sclerosis. Nevertheless, how the VCP activities were regulated and how the pathogenic mutations affect the function of VCP during stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 67 publications
(74 reference statements)
2
55
0
Order By: Relevance
“…Although NMDA receptors were best characterized as a postsynaptic component to relay excitatory potentials, mounting evidence has shown that presynaptic NMDA receptors are widely present in the CNS (Bouvier et al, 2015). At excitatory terminals, NMDA receptors could be activated by glutamate released from axon terminals as autoreceptors to increase calcium influx and to further regulate neurotransmitter release and excitotoxicity (Suárez et al, 2005;Bouvier et al, 2015). Our results support a model whereby C9 DPRs could stimulate synapses' overgrowth, promote glutamate release, and activate presynaptic NMDA receptors to exacerbate excitotoxicity.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Although NMDA receptors were best characterized as a postsynaptic component to relay excitatory potentials, mounting evidence has shown that presynaptic NMDA receptors are widely present in the CNS (Bouvier et al, 2015). At excitatory terminals, NMDA receptors could be activated by glutamate released from axon terminals as autoreceptors to increase calcium influx and to further regulate neurotransmitter release and excitotoxicity (Suárez et al, 2005;Bouvier et al, 2015). Our results support a model whereby C9 DPRs could stimulate synapses' overgrowth, promote glutamate release, and activate presynaptic NMDA receptors to exacerbate excitotoxicity.…”
Section: Discussionsupporting
confidence: 64%
“…commonly considered a noncell-autonomous event caused by the loss of glial glutamate transporter or altered expression of AMPA receptors (Cleveland and Rothstein, 2001). Recent studies using C9 patient-derived iPSCs motor neurons showed increased susceptibility of these neurons to glutamate toxicity, likely contributed by AMPA receptor activation Selvaraj et al, 2018;Shi et al, 2018) and/or decreased glutamate uptake by astrocytes (Shi et al, 2018). Interestingly, in our in vivo model of C9 DPRs, we have found that a presynaptic cellautonomous mechanism in glutamatergic neurons contributes to the neurodegenerative phenotypes.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…Pathogenic mutation of sumoylated residues in valosin‐containing protein/p97 inhibits its translocation to the nucleus, the formation of stress granules, reduction of hexamer formation, and eventually, inhibition of its clearance. The amino acid substitutions for these mutants are prevalent in FTDs [48].…”
Section: Types Of Minimotifs In Neurodegenerative Diseasesmentioning
confidence: 99%